The LIFTMOR-M (Lifting Intervention For Training Muscle and Osteoporosis Rehabilitation for Men) trial: protocol for a semirandomised controlled trial of supervised targeted exercise to reduce risk of osteoporotic fracture in older men with low bone mass - Benjamin K Weeks; Belinda R Beck; Amy T Harding; Steven L Watson (BMJ Open)
Introduction The primary aim of the proposed study is to examine the efficacy of an 8-month supervised, high-intensity progressive resistance training and impact loading programme in comparison with a supervised machine-based isometric exercise training programme using the bioDensity system in older men with low bone mass. We will also determine the safety and acceptability of each exercise training mode. Intervention group responses will be compared with those of a self-selected, non-randomised control sample of sex-matched and age-matched men who will follow their usual lifestyle activities for 8 months.Methods and analysis Apparently healthy men over 50 years with low bone mass, screened for medical conditions and medications known to adversely affect bone health, will be recruited. Eligible participants will be randomly allocated to 8 months of either exercise programme with block randomisation based on presence or absence of osteoporosis medications. A twice-weekly, 30-minute, supervised exercise programme will be conducted for both groups. The primary outcome will be change in femoral neck areal bone mineral density determined by dual-energy X-ray absorptiometry (DXA). Secondary outcomes, assessed at baseline and 8 months, will include: DXA-derived whole-body, bilateral proximal femur and lumbar spine areal bone mineral density; proximal femur bone geometry and volumetric density extracted using three-dimensional hip analysis software; anthropometry; body composition; kyphosis; vertebral fracture assessment; physical function; safety (adverse events and injuries); and compliance. Intention-to-treat and per-protocol analyses will be conducted.Discussion Whether a high-intensity, low-repetition progressive resistance training and impact loading programme or a machine-based isometric exercise programme can improve determinants of fracture risk, without causing injury, has not been examined in men. Determination of the efficacy, safety and acceptability of such programmes will facilitate formulation of future exercise guidelines for older men with low bone mass at risk of fragility fracture, a group who have previously been under-represented.Ethics and dissemination Participant confidentiality will be maintained with publication of results. The study has been granted ethical approval from the Griffith University Human Research Ethics Committee (Protocol number AHS/07/14/HREC).Trial registration number Australian New Zealand Clinical Trials Registry (www.anzctr.org.au)ANZCTR12616000344493; Pre-results.